Knowledge, awareness and perception of Natural Procreative Technology (NaProTechnology) among pharmacy undergraduate students in Nigeria: a pre-post educational video intervention study - Abdulmuminu Isah; Adaobi Uchenna Mosanya; Eziamaka Pauline Ezenkwele; Fausta Chioma Emegoakor; Mmaduabuchi Okeh (BMJ Open)
Objective The study assessed the knowledge, awareness and perception of NaProTechnology as well as the effect of an educational video intervention among pharmacy undergraduate students.Design The study design was a pre-post educational video intervention using a cross-sectional questionnaire-based survey.Participants and setting The study was done among undergraduate students of a school of pharmacy in South-eastern Nigeria.Intervention and outcome measures At baseline, the knowledge, awareness and perception of the students were assessed using a 17-item questionnaire: five questions for knowledge, five questions for awareness and seven questions for perception, followed by the administration of an educational video on NaProTechnology which was prepared by one of the authors, a gynaecologist and also an expert in NaProTechnology. A post-intervention survey was done with the same pre-intervention questionnaire to assess the effect of the educational intervention. The correct (knowledge) or positive (awareness and perception) responses for each question were reported as percentages.Results There were 410 and 350 students in the pre- and post-intervention surveys, respectively, with a relatively equal number of males and females. The majority were between 18 and 29 years old. The average proportion of the participants with correct responses on the knowledge assessment of NaProTechnology was 13.2% and 75.7% in the pre- and post-intervention surveys, respectively (p<0.0001).Conclusion An educational video intervention was effective in improving the short-term knowledge, awareness and positive perception of NaProTechnology among pharmacy students.